PENGARUH BUDAYA ORGANISASI KLIEN DAN KOMPETENSI AUDITOR TERHADAP AUDIT JUDGEMENT - Jusmatang, A. (Institut Agama Islam Negeri (IAIN) Bone, 2023)
The study aims to examine and analyze the influence of organizational culture clients such as management support, the direction of the company, reward systems, communication patterns, and auditor competence such as knowledge and experience affect in making audit judgements on auditors who works in a public accountant firm of Makassar partially or simultaneously. Data used is a primary data in form of a questionnaire. The analysis method used to multiple linear regression with the help analysis in form of a statistical product and service solution 16, where this analysis based on data of 40 respondents who have completed the entire statement in questionnaire. The results of this study indicate that the organization culture client and auditor competence positively affect on audit judgement simultaneously and partially.